PENYELESAIAN SENGKETA ALTERNATIF PADA SENGKETA KONSUMEN - Ari Purwadi (Institute for Research and Community Services (LPPM) of Wijaya Kusuma Surabaya University, 2004)
Settling customer dispute can be done using out of court dispute settlement in conciliation, mediation, and arbitration ways. Initial step in settling the customer dispute done using negotiation model. The process of out of court dispute settlement utilizes alternative dispute resolution for civil responsibility aspect.